Economic viability and energy use in legume-zero-till maize (Zea mays) cropping system under nitrogen fertility levels in irrigated conditions - KISHORE, A SAI; SREELATHA, D; REDDY, M MALLA; KUMAR, M V NAGESH; KUMAR, T SUKRUTH (The Indian Journal of Agricultural Sciences, 2025)
Recent advancement in pulse production supplementing cereal as a year-round productivity with suboptimal fertilizer using the residual waste as means of cost subjugation for sustainable resource cycle was analyzed in zero-till conditions on cost effectiveness and energy balance sheets. The present study was carried out during rainy (kharif) and winter (rabi) season of 2021–22 and 2022–23 at Professor Jayashankar Telangana Agricultural University, Rajendranagar, Hyderabad, Telangana to evaluate the economic aspects influenced by the preceding legumes on rabi maize. The experiment was laid out in a split plot design (SPD) in 3 replications. Treatments were framed with 6 main-plots, viz. C1N1, Groundnut (Arachis hypogaea) 100%RDN- maize (Zea mays L.); C1N2, Groundnut75%RDN- maize; C2N1, Soybean (Glycine max L.)100%RDN- maize; C2N2, Soybean75%RDN- maize; C3N1, Greengram (Vigna radiata L.)100%RDN- maize; C3N2, Greengram75%RDN- maize and 3 sub-plots, viz. 100% RDN, 125% RDN, 150% RDN. The output data signified higher individual (1,28,463 ₹/ha) and overall net returns (2,09,902 ₹/ha), B-C ratio (3.41), system profitability (1043 ₹/ha/day), productivity (70.93 kg/ha/day) and energetics viz. energy ratio, net energy (2,87,660 MJ/ha), energy productivity (0.580 Kg/MJ × 103) with prior green gram with 100% RDN on rabi maize followed by soybean and groundnut, respectively. Subsequently with nitrogen levels, 150% RDN showed its supremacy in output economical and energy balance sheets over lesser doses (125% and 100% RDN). However, interaction among the treatments i.e. (legume residues × nitrogen levels in rabi) was statistically found to be non- significant in 2 years of study.